The application of microneedles fabricated by diffraction ultraviolet (uv) lithography - Li, Yuankai (Kansas State University, 2023)
This report summarizes a series of research results based on UV-light microneedles manufacturing technology. The content can be divided into three parts: Discussing the effect of wavelength on UV lithography microneedle fabrication results, a fabrication process of a wound patch that includes an array of light-focusing microneedle and self-actuatable and light-filtering hydrogel, and fabrication of hollow microneedle and hollow-well microneedle. UV diffraction lithography has been introduced as a rapid and batch-friendly microneedle fabrication method. The shape and aspect ratio can be defined by masks with variable patterns. The shape of the UV light source is changed through the mask, and different patterns are mapped on the photosensitive material layer so as to make various 3d structures. In this manufacturing process, we found that the wavelength of the light source can affect the experimental results. Therefore, the research began by testing the relationship between wavelength and the shape of microneedles fabricated by UV lithography. After that, I joined the MAP (Microneedle-array patch) project. In this project, all the microneedles we used were fabricated by UV lithography. As mentioned above, the MAP project is trying to develop a wound-healing microneedle array that loads 9 solid microneedles. Solid microneedles are only one type of microneedle. In order to increase the functionality of the microneedles array, we also Explore the method of fabricating hollow-well microneedles.
Keywords: Microneedle